Considering the Intercultural Development Inventory (IDI) to Assess Intercultural Competence at U.S. Pharmacy Schools - Diana Tamer; Yifei Liu; Jennifer Santee (MDPI AG, 2023)
Background: U.S. pharmacy schools need to engage in improving intercultural competence among administrators, faculty, staff, and students. The Intercultural Development Inventory (IDI) can be a possible tool to determine the level of intercultural competence. U.S. pharmacy schools need to examine the validity of the IDI within the context of health professional education prior to using this tool. Objectives: To describe the relationship between the IDI and its underlying theory, identify whether the validity of the IDI has been established within two specific contexts, and discuss the practical issues and implications of using the IDI. Methods: Medline, Embase, and selected health professional education journal websites were searched to identify fully published studies utilizing the IDI within health professional education. Eligibility of articles was determined with a standardized approach. Results: Ten studies were identified by full-text reviews, but none investigated the validity of the IDI. Conclusions: The IDI has been shown to be valid in certain contexts, but its validity has yet to be confirmed within health professional education. U.S. pharmacy schools need to examine practical issues and implications when deciding if the resources required to administer, analyze, and report IDI results are reasonable.